DISEASE MANAGEMENT OF LATE BLIGHT POTATO WITH PLANT EXTRACTS - DEVESH NAGAR; S. K. BISWAS; RAVINDRA SINGH; MORAJDHWAJ SINGH; JASKARAN SINGH; VIRENDRA KUMAR; KISHAN LAL (The Bioscan, 2015)
Plant extracts viz. Salix sp., Achyranthusaspera, Solanumnigrum, Partheniumhysterophorus, Daturastramonium, Melilotusalbus, Convolvulus arvensis and Lantana camaraastuber treatment and foliar spray significantly in- creased seed germination from 71 – 86 % and plant height with the highest is noted in case of Lantana camaratreated plant showing 86.34% and 20.2 cm against 71.0 % and 10.4 cm respectively in case of control. Biochemical analysis of treated plant showed that there was increase content of soluble protein and total phenol content.The maximum soluble protein content was found in Lantana camera treated plant showing 32.62 mg/g of fresh leaves against 21.57 mg/g of fresh leaves in case of control. Similarly, high content of phenols was also recorded in Partheniumhysterophorus treated plant representing 2.28 mg/g of fresh leaves against 1.52 in control at 15 days of inoculation. The disease severity showed negative correlation with soluble protein (r=-0.5486) and total phenol (r=-0.3225) at 15 days of pathogenic inoculation. Thus the plant extracts have ability not only to increase seed tuber germination and plant growth promotion but also synthesized defense molecules (Protein & Phenol) in plant resulted decline disease severity from 96.12 – 8.93 per cent.